Penyelesaian Kasus Kekerasan Dalam Rumah Tangga Melalui Restorative Justice di Polda Sumut - Artha Sebayang; Utary Maharany Barus; M. Citra Ramadhan (Mahesa Research Center, 2021)
The purpose of this study was to determine the legal rules of restorative justice in the settlement of cases of Domestic Violence (KDRT) at the North Sumatra Regional Police. According to Law Number 2 of 2002 concerning the Police and the factors that cause restorative justice to not work. Research on the Settlement of Domestic Violence Cases through Restorative Justice the North Sumatra Police Case Study is a normative legal research. Normative legal research aims to examine library legal materials. In the Domestic Violence Law No. 23 of 2004 which is a criminal act of complaint and the reporter and victim are people who live within the scope of the household, but the law only confirms that there are no criminal provisions prioritizing the settlement of restorative justice for domestic violence which is minor and constitutes a criminal complaint. The concept of restorative justice is another method used to handle criminal cases. This concept prioritizes the integrity of perpetrators, victims and society as a unit to find solutions and return to a good relationship pattern between victims and perpetrators of criminal acts and one way that can be done in this concept is penal mediation.